Contrasted modifications of IgM and IgT repertoires induced by high- and low-virulent infectious pancreatic necrosis virus strains in rainbow trout (Oncorhynchus mykiss) - Navelsaker Thommessen, Sofie; Jouneau, Luc; Castro, Rosario; Mhanna, Vanessa; Mariotti-Ferrandiz, Encarnita; Munang´andu, Hetron M.; Gamil, Amr Ahmed Abdelrahim; Collet, Bertrand; Boudinot, Pierre; Evensen, Oystein (Frontiers in Immunology, 2026)
IntroductionInfectious pancreatic necrosis virus (IPNV) is a significant pathogen in salmonid aquaculture, with virulence determined mainly by amino acid residues in the VP2 capsid protein.MethodsThis study investigates the modifications of rainbow trout (Oncorhynchus mykiss) IgM and IgT repertoire induced by two IPNV strains that differ at VP2 positions 217 and 221, specifically IPNV-TA (T217A221) and IPNV-PT (P217T221). For these studies, doubled-haploid isogenic trout were immunised with IPNV-TA or IPNV-PT, and IgHμ and IgHτ repertoires were analysed by high-throughput sequencing.ResutlsWe demonstrated that IPNV-PT elicited a strong and diverse modification if the IgM repertoire in the spleen, with significant clonotypic expansions including public components, particularly within VH1, VH4, and VH8 subgroups, observed two months post-immunization. Despite this robust response, clonotype usage largely reflected a non-convergent immune profile, consisting essentially of private responses, with limited sharing across individuals. In contrast, IPNV-TA triggered only modest changes in the repertoire. Notably, the IgM response to IPNV-PT diminished by four months, with limited persistence of public clonotypes. Changes of spleen IgT repertoire remained limited.DiscussionThese findings demonstrate that even minor VP2 variations can profoundly affect not only the magnitude but also the clonal architecture and composition of antiviral B cell responses, highlighting the importance of detailed, strain-specific immune profiling in guiding vaccine development for aquaculture.